Measurement and correlation for phase equilibrium of HFO1234yf with three pentaerythritol esters from 293.15 K to 348.15 K. (September 2017) - Sun, Yanjun; Wang, Xiaopo; Wang, Dongbo; Jin, Liwen
Highlights: The phase equilibrium of R1234yf in PEC6, PEC7, and PEC8 have been measured based on the isochoric method. The data were correlated using the PR EoS with HVOS mixing rules and Wilson equation. The solubilities of R1234yf in different PECs were compared and analyzed. Abstract: 2, 3, 3, 3-Tetrafluoroprop-1-ene (HFO1234yf) is recently recognized as a new generation refrigerant to replace R134a in automotive air-conditioning system and other refrigeration applications. The knowledge of phase equilibrium property for refrigerant with lubricant oil is therefore interested in these systems. A systematic research program on the phase equilibrium of HFO1234yf with lubricant oils has been carried out in our laboratory, and the purpose is to investigate the influence of the molecular structure of oils, pressure and temperature on the phase behavior of HFO1234yf and lubricant oil system. In this work, the measurements of phase equilibrium for HFO1234yf + pentaerythritol tetrahexanoate (PEC6), HFO1234yf + pentaerythritol tetraheptanoate (PEC7), and HFO1234yf + pentaerythritol tetraoctanoate (PEC8) between 293.15 K and 348.15 K were performed by means of isochoric saturation method. The experimental data were correlated using the PR EOS and HVOS mixing rule combined with Wilson excess free-energy model. The average relative deviations between experimental results and the calculated pressure by the model for HFO1234yf + PEC6, HFO1234yf + PEC7, and HFO1234yf + PEC8 system were 1.23%, 1.19%, and 1.39%, respectively. The maximum relative deviations were 4.04%, 4.34%, and 4.84%, respectively.